Endurance training stimulates growth and survival pathways and the redox balance in rat pancreatic islets - Calegari, Vivian C.; Abrantes, Julia L.; Silveira, Leonardo R.; Paula, Flavia M.; Costa, Jose Maria; Rafacho, Alex; Velloso, Licio A.; Carneiro, Everardo M.; Bosqueiro, Jose R. [UNESP]; Boschero, Antonio C.; Zoppi, Claudio C. (Amer Physiological Soc, 2012)
Calegari VC, Abrantes JL, Silveira LR, Paula FM, Costa JM Jr, Rafacho A, Velloso LA, Carneiro EM, Bosqueiro JR, Boschero AC, Zoppi CC. Endurance training stimulates growth and survival pathways and the redox balance in rat pancreatic islets. J Appl Physiol 112: 711-718, 2012. First published December 15, 2011; doi:10.1152/japplphysiol.00318.2011.-Endurance training has been shown to increase pancreatic beta-cell function and mass. However, whether exercise modulates beta-cell growth and survival pathways signaling is not completely understood. This study investigated the effects of exercise on growth and apoptotic markers levels in rat pancreatic islets. Male Wistar rats were randomly assigned to 8-wk endurance training or to a sedentary control group. After that, pancreatic islets were isolated; gene expression and the total content and phosphorylation of several proteins related to growth and apoptotic pathways as well as the main antioxidant enzymes were determined by real-time polymerase chain reaction and Western blot analysis, respectively. Reactive oxygen species (ROS) production was measured by fluorescence. Endurance training increased the time to reach fatigue by 50%. Endurance training resulted in increased protein phosphorylation content of AKT (75%), AKT substrate (AS160; 100%), mTOR (60%), p70s6k (90%), and ERK1/2 (50%), compared with islets from control group. Catalase protein content was 50% higher, whereas ROS production was 49 and 77% lower in islets from trained rats under basal and stimulating glucose conditions, respectively. Bcl-2 mRNA and protein levels increased by 46 and 100%, respectively. Bax and cleaved caspase-3 protein contents were reduced by 25 and 50% in islets from trained rats, respectively. In conclusion, these results demonstrate that endurance training favors the beta-cell growth and survival by activating AKT and ERK1/2 pathways, enhancing antioxidant capacity, and reducing ROS production and apoptotic proteins content.
Keywords: AKT; ERK; redox status; caspase-3; Bcl-2/Bax ratio